A Bilinear Map Pairing Based Authentication Scheme for Smart Grid Communications: PAuth - Yuwen Chen (IEEE Access, 2019)
Smart meters have been widely applied in the smart grid, and they enable two-way communication in the smart grid. User's electricity consumption data and other data are transmitted between the entities. It is necessary to ensure the security of this two-way communication. Several authentication schemes have been proposed to solve this problem. Recently, Mahmood et al. proposed an authentication scheme for the smart grid. However, we find that their scheme cannot provide the perfect forward secrecy and private key privacy as they have claimed. An improved version by Abbasinezhad is found to be subject to replay attack, too. In this paper, a bilinear map pairing-based authentication and key establish scheme is proposed, which can withstand the aforementioned attacks and achieves more security features, private key privacy, perfect forward privacy, and message integrity. We designed a simpler registration scheme, which implements the same functionalities, while the computation cost is reduced. We also conducted a formal security analysis of the proposed scheme, and the result shows that the proposed scheme is secure. Our simulation results show that the proposed scheme has a comparable communication cost and computation cost.